Sediments accretion at Guarapiranga reservoir, metropolitan region of São Paulo, Brazil, by the 210Pb chronological method - Bonotto, D. M. [UNESP]; Sabaris, T. P.P.; Bicudo, D. C.; Bicudo, C. E.M.; Fontana, L. (Springer Nature, 2022)
The Constant Flux: Constant Sedimentation (CF:CS) and Constant Rate of Supply (CRS) of unsupported/excess 210Pb models have been applied to a 210Pb data set providing of two sediments profiles (GUA-T1 and GUA-T2) sampled at Guarapiranga reservoir, in the Metropolitan Region of São Paulo city, São Paulo State, Brazil. Sedimentation rates obtained by the CF:CS model corresponded to 9.3–12.3 and 30 mg.cm− 2yr− 1, respectively, for profiles GUA-T1 and GUA-T2, indicating a better chronological performance relatively to that of the CRS model in the study area, also allowing successful estimates of the P fluxes in the reservoir.
Keywords: 210Pb chronological method; CF:CS and CRS methods; Guarapiranga reservoir; P fluxes; Sedimentation rates